Haemophilia Registry of the Medical Committee of the Swiss Haemophilia Society - Brand, B.; von der Weid, N. (Hämostaseologie, 2009)
The Swiss Haemophilia Registry of the Medical Committee of the Swiss Haemophilia Society was established in 2000. Primarily it bears epidemiological and basic clinical data (incidence, type and severity of the disease, age groups, centres, mortality). Two thirds of the questions of the WFH Global Survey can be answered, especially those concerning use of concentrates (global, per capita) and treatment modalities (on-demand versus prophylactic regimens). Moreover, the registry is an important tool for quality control of the haemophilia treatment centres.There are no informations about infectious diseases like hepatitis or HIV, due to non-anonymisation of the data. We plan to incorporate the results of the mutation analysis in the future.
Keywords: Haemophilia; registry; treatment modality; factor use; quality control